Economics Teachers’ Awareness and Response to Curriculum Changes in Banjarmasin and Barito Kuala - Dwi Atmono; Edy Suryanto; Muhammad Rahmattullah; Rochman Hadi Mustofa (Economics Education Department Universitas Negeri Semarang, 2026)
This study investigates the awareness levels of economics teachers in senior high schools regarding curriculum changes in the digital era, with a focus on internet use in Banjarmasin City and Barito Kuala (Batola) Regency, South Kalimantan, Indonesia. Using a survey research design, data were gathered through documentation and questionnaires to measure teachers’ self-efficacy and concerns in adopting e-learning practices. The population of this study was all economics teachers in the two regions, while the sample consisted of selected economics teachers who participated in the survey. The study refers to curriculum changes within the framework of the Indonesian national curriculum, particularly the transition toward the Kurikulum 2013 (K13) and digital-based learning adaptation in the current curriculum policy. Results show that teachers’ overall internet self-efficacy is moderate, with an average score of 3.73 on a 6-point Likert scale. Teachers rated reading texts from websites highest (4.15), while creating simple webpages with text, images, and links was rated lowest (2.65). About 54.76% of economics teachers actively engaged in e-learning, reaching the management (2.38%), consequence (21.43%), collaboration (9.52%), and refocusing (21.43%) stages of concern. A significant positive correlation exists between internet self-efficacy and levels of concern in implementing e-learning. The findings highlight the importance of boosting teachers’ confidence in using digital tools to increase their engagement with e-learning. It is recommended that economics education programs raise awareness of digital-era curriculum changes, provide practical e-learning resources, and offer continuous mentoring to help teachers effectively integrate technology into their teaching practices.